PELATIHAN DAN PENDAMPINGAN TATA DISPLAY TOKO: SEBAGAI UPAYA IDENTIFIKASI RISIKO BISNIS - Halid Hasan; Abdul Waris; Izzatul Ulya; Zhulvardyan Armayrishtya (Dharma: Jurnal Pengabdian Masyarakat, 2023)
Store display is an important component in the retail business segment. Business actors must be able to create attractive spatial planning and product arrangement through store displays so that consumers feel at home and comfortable when shopping. Effective arrangement in addition to increasing sales can also minimize the risk of loss. Such as avoiding loss of goods, theft, inaccurate records, and others. This activity was delivered to the Delfa Store which is located at Jl. Kenanga Kav.2, Mulyoagung Village, Kecamatan Dau Kabupaten Malang. Based on preliminary observations, it was found that the display conditions in stores that sell various household goods are still not good.  So that it becomes difficult to develop and there is uncertainty about business continuity in the future. This is the background for carrying out this activity, by analyzing the condition of store displays as an effort to identify business risks.